Does Transformational Leadership Promote Employee Perceptions of Ethical Leadership?: A Moderated Mediation Model of Procedural Justice and Power-Distance Orientation - Lee, Junghyun; Cho, Jeewon; Pillai, Rajnandini (Journal of Leadership, Accountability and Ethics, 2020)
This study examines three primary research questions: (1) if transformational leadership predicts followers’ subsequent perceptions of ethical leadership as time elapses; (2) which boundary conditions affect the relationship between justice perceptions, derived from the leader’s transformational characteristics, and ethical leadership; and (3) what the relationships are between ethical leadership and follower outcomes (job satisfaction, affective commitment and objective performance appraisals). Using the data collected through a three-wave survey over a two-year period, we found that transformational leadership was positively related to ethical leadership via procedural justice and this mediated relationship was stronger for followers with lower power-distance orientation